2014
DOI: 10.1080/03630242.2014.899543
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Related to Posttraumatic Growth in Breast Cancer Survivors: A Review

Abstract: In this article, we reviewed quantitative studies regarding psychosocial factors associated with posttraumatic growth (PTG) in patients with breast cancer to elucidate our understanding of a model of PTG process. PsycInfo, Embase, Medline, Web of Knowledge were used for the search. Only quantitative, English written studies that used the Posttraumatic Growth Inventory (PTGI) measure administered to breast cancer patients were included. The initial search yielded 90 publications. Of those, 22 studies satisfied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 37 publications
6
41
1
5
Order By: Relevance
“…These effects negatively affect their health‐related quality of life , and over 25% of HNC survivors suffer from clinical levels of distress . However, in this population, moderate to high levels of PTG have consistently been found , which are comparable to levels of PTG in other cancer populations . In a systematic review including five studies, Harding and colleagues identified several factors that seem to be associated with PTG in HNC survivors: younger age at diagnosis, relationship status, positive reframing, optimism, and hope .…”
Section: Introductionmentioning
confidence: 99%
“…These effects negatively affect their health‐related quality of life , and over 25% of HNC survivors suffer from clinical levels of distress . However, in this population, moderate to high levels of PTG have consistently been found , which are comparable to levels of PTG in other cancer populations . In a systematic review including five studies, Harding and colleagues identified several factors that seem to be associated with PTG in HNC survivors: younger age at diagnosis, relationship status, positive reframing, optimism, and hope .…”
Section: Introductionmentioning
confidence: 99%
“…Wiele badań wskazuje na pozytywną rolę optymizmu w procesie wzrostu po traumie, także u chorych onkologicznie. Dodatni związek optymizmu z występowaniem pozytywnych zmian potraumatycznych stwierdzono u kobiet zmagają-cych się z rakiem piersi [8,[17][18][19], u osób po przeszczepie szpiku kostnego [20], u chorych na raka jamy ustnej [21], raka wątroby [22] czy zmagają-cych się z chorobą nowotworową będących w stanie terminalnym [23]. Należy jednak podkreślić, że dostępne są wyniki badań, w których nie stwierdzono związku między optymizmem a rozwojem po traumie.…”
Section: Przekonania I Oczekiwaniaunclassified
“…A large literature suggests that many cancer patients perceive positive changes related to their illness experience (Kolokotroni, Anagnostopoulos, & Tsikkinis, 2014; Shand, Cowlishaw, Brooker, Burney, & Ricciardelli, 2015; Stanton, Bower, & Low, 2006). Various terms have been used to describe these changes, including posttraumatic growth, stress-related growth, and benefit finding.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the psycho-oncology literature has largely focused on positive changes in early-stage breast cancer patients (Danhauer et al, 2013; Kolokotroni et al, 2014; Wang et al, 2015) and their spousal caregivers (Manne et al, 2004; Weiss, 2004). However, recent studies have examined positive changes in patients and caregivers coping with various cancers (Arpawong, Richeimer, Weinstein, Elghamrawy, & Milam, 2013; Moore et al, 2011; Salsman, Segerstrom, Brechting, Carlson, & Andrykowski, 2009; Thornton et al, 2012).…”
Section: Introductionmentioning
confidence: 99%